2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31133
|View full text |Cite
|
Sign up to set email alerts
|

The Use of SPICE Simulation to Promote Reflection and Metacognition in a Microelectronics Course

Abstract: His general research interests lie in the area of electronics, circuits and embedded systems and in particular, technologies in those areas that have biomedical applications. He has expertise in the design and simulation of mixed-signal integrated circuits and systems that incorporate the use of both digital and analog electronics, as well as optics, microfluidics and devices that interface to the biological world. Prior to joining the University of Pittsburgh faculty he was a co-founder and the president of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The findings of this study are somewhat in line with the results of the study by Clark and Dickerson [9], which found that students struggled to reach levels of critical reflection, which is characterized by "a change in perspective over a fundamental belief" [9, p. 11]. In the present study, it was found that while some students were able to reach high levels of metacognitive strategies, for all metacognitive strategies (with the exception of transfer), the majority of responses were coded as either low or medium.…”
Section: Overallsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study are somewhat in line with the results of the study by Clark and Dickerson [9], which found that students struggled to reach levels of critical reflection, which is characterized by "a change in perspective over a fundamental belief" [9, p. 11]. In the present study, it was found that while some students were able to reach high levels of metacognitive strategies, for all metacognitive strategies (with the exception of transfer), the majority of responses were coded as either low or medium.…”
Section: Overallsupporting
confidence: 92%
“…Two studies have investigated used the exam analysis & reflection (EAR) method in which university students identify the mistakes they made on exams and correct their mistakes [8], [9]. In both studies, results did not show a significant difference between students' performance before and after engaging in EAR [8], or the performances of students who did and did not engage in EAR [9]. In the study by Roldan [10] undergraduate students were interviewed about how they understood and engaged in reflection.…”
Section: B Metacognition At the University Levelmentioning
confidence: 99%
“…Reflection activities can be used in a course to achieve different objectives: metacognition, competency, and personal growth and change (Reflection Activities, n.d.). A few studies have implemented a guided reflection exercise called Exam Analysis and Reflection (EAR) in a mechanical engineering course (Benson & Zhu, 2015), an electrical circuit course (Claussen & Dave, 2017), and a microelectronic course (Clark & Dickerson, 2018) to investigate the effectiveness of reflection on students' performance and learning. The results of Benson and Zhu (2015) and Claussen and Dave (2017) emphasized the need for a more thorough integration of the reflection activity in the course, whereas Clark and Dickerson (2018) concluded that the effectiveness of reflection is sensitive to exam problem type.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clark and Dickerson [16] studied the impact of using an adapted EAR exercise that incorporated SPICE (Simulation Program with Integrated Circuit Emphasis) simulation tools in a microelectronic course. Students compared their exam answers to the SPICE simulation results to identify their mistakes.…”
Section: Reflection Practices In Stem Coursesmentioning
confidence: 99%